Exclusive Economic Zone (EEZ): Securing Indonesia’s Future Under the 1982 United Nations Convention on the Law of the Sea - Dilla Hariyanti; Mugiati Mugiati (International Journal Labs, 2026)
The Exclusive Economic Zone (EEZ) has economic value, it is not uncommon for a conflict between intersecting countries such as between Indonesia and Malaysia over the islands of Sipadan and the island of Ligitan. Between Indonesia and Vietnam, there is a territorial dispute in the waters around the Natuna Islands. In the occurrence of conflicts in the EEZ boundary area, the Government must better anticipate the occurrence of disputes by making efforts to strengthen the position of state sovereignty and law enforcement in the EEZ. Problem Formulation: 1. How is the sovereignty of the Republic of Indonesia as an archipelagic country in managing and utilizing the Exclusive Economic Zone? 2. Can the law enforcement carried out by the Indonesian government to be able to guarantee the natural resources contained in the Exclusive Economic Zone Area can meet the survival of the nation? Using normative legal research. Indonesian state sovereignty in the international system is the recognition of another country over the country's border areas in the EEZ and has the sovereign right to explore, exploit, conserve and manage natural resources both biological and non-biological and waters above the seabed and land below, as affirmed in Article 56 paragraph (1) of the 1982 Convention on the Law of the Sea. The State of Indonesia may take action in the form of boarding a ship, inspecting, arresting and conducting judicial proceedings based on Article 73 paragraph (1) of the 1982 Convention on the Law of the Sea and may carry out an act of instant pursuit (hot pursuit) against a foreign ship if the authorities have sufficient reason to suspect that the ship violates the laws of the State of Indonesia, as stipulated in Article 111 of the 1982 Convention on the Law of the Sea.